Availability and estimation of renewable energy for habitants living in remote places - Muhammad Hazim, Md Yusoff (2010)
Today, the world has been relying on fossil fuels as its primary source of energy. This unsustainable energy source is not going to last long. Thus, the green renewable energy should be practice from now on. Malaysia is gifted with many natural renewable energy resources. It is because it has a long coast line, good rainfall with rivers flowing for greater part of the year. In Malaysia also there are 82% of the remote places in Malaysia have electricity in their place but sometime this electricity is not functional because of the some problem. And for the other 12%, there are not facilities for them. The electricity is very important for our daily life for the cooking, lighting and the others activity. This thesis is presented the research to determine the suitable renewable energy use in remote places which in Malaysia. After some research, there are potential of renewable energy that can be used that is biomass energy, solar energy and wind energy. Based on the parameter in the remote place, the case study has been done for design the system for that habitant to generate the electricity. With the animal dung and excrement, biogas digester can be use. The biogas produce can generated the electricity for that place. But, the number of the animal available is less than number of animal needed for generates the whole place. After that, solar photovoltaic is the one way of the solution for this problem. Solar photovoltaic system can be use with the biogas digester. In other hand, wind turbine also can be one of the alternative ways beside the solar photovoltaic. So, this paper is discussed about the best solution for the remote place to choose the suitable renewable energy either biogas-solar photovoltaic or biogas-wind turbine.